Role of surface layer nanosrtucturing in improving mechanical and corrosion properties of reactor materials - Ozhigov, L.S.; Belous, V.A.; Savchenko, V.I.; Nosov, G.I.; Ovcharenko, V.D.; Tolmachova, G.N.; Kuprin, A.S.; Goltvyanitsa, V.S. (Вопросы атомной науки и техники, 2017)
The results of investigations into the influence of the ion-plasma treatment (IPT), including the ion implantation and ion-plasma coating deposition, on the mechanical properties and corrosion resistance of nuclear fuel cladding tubes made of zirconium alloy (Zr1%Nb) are presented. The tests of cladding samples have been performed at two temperatures between 20 and 350 °С. It is shown that the deposition of TiN, Ti+TiN, TiAlN, TiAlSiN, TiAlYN coatings improves mechanical properties of the sample surface, as well as, leads to the hardening of Zr1%Nb fuel cladding as a whole. The efficiency of hardening by implantation with (Zr, Mo) and gaseous (N₂, O₂) ions depends on the kind of ions and their energy. The nanostructure TiAlSiN and TiAlYN coatings improve the corrosion resistance of zirconium alloy. The results of experiments on hardening of fuel cladding tubes are explained by the state of the coating-surface interface. Представлені результати впливу іонно-плазмової обробки (ІПО), що включає іонну імплантацію і осадження іонно-плазмових покриттів, на механічні властивості і корозійну стійкість зразків з твельних трубок цирконієвого сплаву Zr1%Nb. Випробування проведені при двох температурах: 20 і 350 °С. Показано, що нанесення покриттів TiN, Ti+TiN, TiAlN, TiAlSiN, TiAlYN призводить до різного підвищення механічних властивостей не тільки поверхні зразків, але і до об'ємного зміцнення трубок зі сплаву Zr1%Nb. Ефективність зміцнення при імплантації металевими (Zr, Mo) і газовими (N₂, O₂) іонами залежить від виду і енергії іонів. Наноструктурні покриття TiAlSiN, TiAlYN збільшують корозійну стійкість цирконієвого сплаву в два рази. Отримані експериментальні результати по зміцненню твельних трубок пояснюються станом інтерфейсу між покриттям і підкладкою. Представлены результаты влияния ионно-плазменной обработки (ИПО), включающей ионную имплантацию и осаждение ионно-плазменных покрытий, на механические свойства и коррозионную стойкость образцов из твэльных трубок циркониевого сплава Zr1%Nb. Испытания проведены при двух температурах: 20 и 350 °С. Показано, что нанесение покрытий TiN, Ti+TiN, TiAlN, TiAlSiN, TiAlYN приводит к различному повышению механических свойств не только поверхности образцов, но и к объемному упрочнению трубок из сплава Zr1%Nb. Эффективность упрочнения при имплантации металлическими (Zr, Mo) и газовыми (N₂, O₂) ионами зависит от вида и энергии ионов. Наноструктурные покрытия TiAlSiN, TiAlYN увеличивают коррозионную стойкость циркониевого сплава. Полученные экспериментальные результаты по упрочнению твэльных трубок объясняются состоянием интерфейса между покрытием и подложкой.